Antibiogram, Prevalence of OXA Carbapenemase Encoding Genes, and RAPD-Genotyping of Multidrug-Resistant Acinetobacter baumannii Incriminated in Hidden Community-Acquired Infections - Waleed El-Kazzaz; Lobna Metwally; Reham Yahia; Najwa Al-Harbi; Ayat El-Taher; Helal F. Hetta (MDPI AG, 2020)
Acinetobacter spp. has gained fame from their ability to resist difficult conditions and their constant development of antimicrobial resistance. This study aimed to investigate the prevalence, susceptibility testing, OXA carbapenemase-encoding genes, and RAPD-genotyping of multidrug resistant Acinetobacter baumannii incriminated in hidden community-acquired infections in Egypt. The antimicrobial susceptibility testing was assessed phenotypically using Kirby-Bauer disk diffusion method. Also, Modified-Hodge test (MHT) was carried out to detect the carbapenemases production. Multiplex-PCR was used to detect the carbapenemase-encoding genes. Furthermore, the genetic relationship among the isolated strains was investigated using RAPD fingerprinting. The bacteriological examination revealed that, out of 200 Gram-negative non-fermentative isolates, 44 (22%) were identified phenotypically and biochemically as Acinetobacter spp. and 23 (11.5%) were molecularly confirmed as A.baumannii. The retrieved A.baumannii strains were isolated from urine (69%), sputum (22%), and cerebrospinal fluid (csf) (9%). The isolated A. baumannii strains exhibited multidrug resistance and the production rates of carbapenemases were 56.5, 60.9, and 78.3% with meropenem, imipenem, and ertapenem disks, respectively. The blaOXA-24-like genes were the most predominant among the tested strains (65.2%), followed by blaOXA-23 (30.4%) and blaOXA-58 (17.4%), in addition, the examined strains are harbored IMP, VIM, and NDM genes with prevalence of 60.9, 43.5, and 13%, respectively, while KPC and GES genes were not detected. RAPD-PCR revealed that the examined strains are clustered into 11 different genotypes at ≥90% similarity. Briefly, to the best of our knowledge, this study is the first report concerning community-associated A. baumannii infections in Egypt. The high prevalence of hidden multidrug-resistant (MDR) and extensively drug-resistant (XDR) A.baumannii strains associated with non-hospitalized patients raises an alarm for healthcare authorities to set strict standards to control the spread of such pathogens with high rates of morbidity and mortality.